The Consistency Between Indonesian National Laws on Wildlife Trade and the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) - Chotimah, Amelinda Qusnul (GoAcademica Research & Publishing, 2024)
The alignment between national legislation and international conservation agreements is critical for effectively managing wildlife trade, especially in biodiversity-rich countries like Indonesia. This article examines the consistency between Indonesian national laws on wildlife trade and the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). Through a review of existing literature and legal analysis, the study identifies significant gaps and challenges in Indonesia's implementation of CITES. Key issues include legal ambiguities, enforcement inconsistencies, and difficulties in verifying the legality of wildlife specimens. The article also explores emerging threats, such as the rise of online wildlife trade, and their implications for both national and international regulatory frameworks. The findings underscore the necessity for Indonesia to enhance its legal and enforcement mechanisms to improve adherence to CITES and contribute more effectively to global conservation efforts.